PENGARUH E-WOM, ONLINE CUSTOMER REVIEW, DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION PRODUK PERAWATAN KULIT LOKAL AVOSKIN: STUDI KASUS MAHASISWI STEI JAKARTA - Irfan Arif Husen; Desy Amaliati Setiawan (Juremi: Jurnal Riset Ekonomi, 2023)
This study aims to determine the influence of e-WOM (X1), online customer reviews (X2), and perceived value (X3) on purchase intention. This research uses the type of associative research with a quantitative approach method. The data collection method uses a questionnaire which is measured using a Likert scale. The population in this study were all Avoskinusers. The sampling method used a purposive sampling technique with the criteria of STEI Jakarta students who had purchased at least one purchase of local Avoskin skin care products. This research was conducted by distributing questionnaires to 102 respondents. Data processing techniques use theSmartPLS 3.2.9 program to test the outer model, inner model and hypotheses .The results of this study indicate that e-WOM has a significant influence on purchase intention, Online Customer Reviews have no significant influence on purchase intention, Perceived Value has a significant influence on Purchase Intention.